Risk factors for amenorrhea in juvenile systemic lupus erythematosus (JSLE): a Brazilian multicentre cohort study - Silva, C. A. A.; Hilario, M. O.; Febronio, M. V.; Oliveira, S. K.; Terreri, M. T.; Sacchetti, S. B.; Sztajnbok, F. R.; Marini, R.; Quintero, M. V.; Bica, B. E.; Pereira, R. M.; Bonfa, E.; et al. (Sage Publications Ltd, 2007)
We evaluated the prevalence and clinical associations of amenorrhea in 298 female juvenile systemic lupus erythematosus (JSLE) patients (ACR criteria) followed in 12 Brazilian Paediatric Rheumatology centres. Amenorrhea was observed in 35 patients (11.7%) with a mean duration of 7.2 +/- 3.6 months. The hormones were performed in 32/35 patients and none of them had FSH and LH levels above and estradiol below the normal range according to pubertal changes. JSLE patients with amenorrhea were younger (15.04 +/- 2.5 versus 17.8 +/- 3.1 years; P = 0.001), and had a shorter period of time between menarche and current age (3.4 +/- 2.9 versus 6.7 +/- 5.4 years; P = 0.001). Interestingly, the frequency, cumulative dose, number of pulses and duration of intravenous cyclophosphamide treatment were alike in patients with and without amenorrhea (P > 0.05). In contrast, patients with amenorrhea had significantly higher SLEDAI (P = 0.01) and SLICC/ACR-DI (P = 0.024) scores compared to those without this condition. Independent risk factors identified by multivariate analysis were higher SLEDAI (OR=1.059; CI=1.004-1.116; P=0.034) and SLICC/ACR-DI (OR=2.125; IC = 1.373-3.291; P = 0.001) scores. Our data suggest that in spite of imummosuppressive therapy, JSLE patients have an adequate ovarian follicular reserve and amenorrhea is particularly associated with disease activity and damage.
Keywords: adolescent; amenorrhea; cyclophosphamide; gonadal function; juvenile systemic lupus erythematosus